PERFORMANCE MODEL OF HEALTH WORKER AT THE JOHAR BARU DISTRICT HEALTH CENTER - Suryadi, Handy; Aima, M. Havidz; W. R, Hernawati; Wiratih, Wiratih; Rohmawati, Siti; Surip, Ngadino (Dinasti Publisher, 2021)
The aim of this study is to identify and explain the influence of culture and training on organizational commitment and its effect on the performance of employees at the District Health Center Johar Baru, Central Jakarta. The research method in this study uses a a causality quantitative approach. The population is all health workers at the Johar Baru Puskesmas with probability sampling techniques and simple random sampling techniques. The data obtained were analyzed using structural equation modeling (SEM) with the Smart PLS version 3.2.8 software program. The results of this study indicate that organizational culture, training and organizational commitment have a significant positive effect on employee performance partially or simultaneously. In addition, organizational commitment mediates organizational culture and performance training. Research suggestions in the aspect of managing performance targets should be arranged in quality and quantity by considering